Community Participation in the Farm Road Development Program in Nagari Gadut, Tilatang Kamang District, Agam Regency, in 2024 - Naila Syakira Putri Hendrya; Yoserizal; Nila Wahyuni (Catalist Indo Publisher, 2026)
Background This qualitative-descriptive study identifies the forms of community participation and its driving factors in the 2024 Sicawan RRI Farming Road Development Program in Nagari Gadut, Agam Regency. Methods Qualitative-Descriptive with grounded in Keith Davis’s participation framework encompassing mind, labor, goods, and money the research utilized interviews, observations, and documentation for data collection. Results Findings reveal that while overall community participation is high, there are significant disparities in intensity across different forms. Labor participation emerged as the most dominant, driven by high enthusiasm for self-managed communal work (gotong royong) and reinforced by nagari policies prioritizing local labor, which reflects strong social capital and local ownership. Furthermore, material (goods) and financial participation were high, effectively addressing budget shortfalls in the Village Fund through transparent management by the Activity Management Team (TPK). Conclusions In contrast,